2022
DOI: 10.1161/circ.146.suppl_1.11506
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 11506: Roles of Mechanical Overload and the Microtubule Network in Mediating T-Tubule Remodeling

Abstract: Background: Mechanical overload is an established contributor to the remodeling of T-tubules (TT) and associated dyssynchronous Ca 2+ release leading to abnormal excitation-contraction coupling in cardiomyopathies. We examined the induction of pathologic TT remodeling in isolated cardiomyocytes and the involvement of microtubules in this process. Methods: Normal adult rat ventricular myocytes (aRVMs) were cultured for 48hrs on MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…What is known, however, is that t-tubule remodeling in cardiomyocytes is one of the hallmarks of HF and an indicator of the disease’s progression. 17–22 In mammals, the β 1 AR and β 2 AR receptor proteins are encoded by the Adrb1 and Adrb2 genes, respectively, both genes having no introns. Several studies highlighted the importance of regulation at the level of mRNA localization and protein synthesis for β 2 AR.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…What is known, however, is that t-tubule remodeling in cardiomyocytes is one of the hallmarks of HF and an indicator of the disease’s progression. 17–22 In mammals, the β 1 AR and β 2 AR receptor proteins are encoded by the Adrb1 and Adrb2 genes, respectively, both genes having no introns. Several studies highlighted the importance of regulation at the level of mRNA localization and protein synthesis for β 2 AR.…”
mentioning
confidence: 99%
“…It has been demonstrated that Adrb2 mRNA, unlike Adrb1, can be initially translationally silent. 18 A 1994 study has shown that the 5′ upstream open reading frame in the Adrb2 mRNA translates into a small peptide product that could inhibit the receptor’s synthesis. 23 A more recent study has demonstrated that in DT1-MF2 and A431 cells, the binding of nucleocytoplasmic shuttling RNA-binding protein HuR to the 3′-UTR of Adrb2 mRNA is crucial in its translational silencing and trafficking to the cell membrane.…”
mentioning
confidence: 99%
See 1 more Smart Citation